2014
DOI: 10.5301/jva.5000214
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Blood Flow as a Predictor of Maturation of Arteriovenous Fistula for Haemodialysis

Abstract: SLF was strongly supportive of successful fistula maturation. A "thrill" was characteristic of spiral rather than turbulence. The mechanism of this apparent beneficial effect of this pattern of flow requires further investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 30 publications
0
25
0
Order By: Relevance
“…Inherent and acquired factors related to vascular dysfunction, such as female sex, diabetes, age older than 65 years, history of peripheral vascular disease, and coronary artery disease, have been linked to early fistula failure. [4][5][6] Moreover, anatomical and surgical factors directly affect the functional outcome. Absence of suitable vascular anatomy, inadequate surgical technique during mobilization of the vein, and lack of surgical expertise have all been identified as contributing factors in AVF failures.…”
Section: Discussionmentioning
confidence: 99%
“…Inherent and acquired factors related to vascular dysfunction, such as female sex, diabetes, age older than 65 years, history of peripheral vascular disease, and coronary artery disease, have been linked to early fistula failure. [4][5][6] Moreover, anatomical and surgical factors directly affect the functional outcome. Absence of suitable vascular anatomy, inadequate surgical technique during mobilization of the vein, and lack of surgical expertise have all been identified as contributing factors in AVF failures.…”
Section: Discussionmentioning
confidence: 99%
“…In clinical practice, these parameters cannot be reliably measured in an outpatient setting. Recent investigation has defined the type of blood flow in a fistula as an important determinate in maturation [ 54 ]. Cannulation techniques and skills must improve.…”
Section: Future Directionsmentioning
confidence: 99%
“…The characteristics of fluidic flow include laminar and disturbed flow, and fluid shear stress increases as the flow become disturbed ( Chien, 2007 ; Chiu and Chien, 2011 ). Cell experiments indicated that laminar flow increases endothelial cell survival, whereas disturbed flow leads to endothelial dysfunction ( Chien, 2008a , b ), followed by smooth muscle cell proliferation and intimal migration ( Paszkowiak and Dardik, 2003 ; Marie et al, 2014 ). Our results demonstrated that among the five different locations of AVF, the highest disturbed flow occurs at the stenotic lesion site.…”
Section: Discussionmentioning
confidence: 99%